2023
DOI: 10.1039/d2mh01358d
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticle-based nanovaccines for cancer immunotherapy

Abstract: Therapeutic cancer vaccines, which are designed to amplify tumor-specific T cell responses, have been envisioned as one of the most powerful tools for effective cancer immunotherapy. However, increasing the potency,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 214 publications
0
27
0
Order By: Relevance
“…[80] This strategy was applied to acute myeloid leukemia; it resulted in the induction of leukemia-specific cytotoxic T lymphocytes and the identification of B1-1 peptide as a novel immunogenic tumorassociated antigen. [81] Mice with CT26 tumors were immunized with DCs co-transfected with GM-CSF mRNA and CT26 whole tumor mRNA; the cytotoxic activity of immunized mice was significantly higher than that of the control group. [64] Mu et al reported that among 19 patients with androgen-resistant prostate cancer that were treated with total tumor-derived mRNA loaded DC vaccines, 8 patients progressed, 11 patients were considered to have stable disease, and 13 patients showed a decrease in serum prostate-specific antigen levels.…”
Section: Dcs Pulsed/enveloped With Whole Tumor Rnamentioning
confidence: 96%
See 1 more Smart Citation
“…[80] This strategy was applied to acute myeloid leukemia; it resulted in the induction of leukemia-specific cytotoxic T lymphocytes and the identification of B1-1 peptide as a novel immunogenic tumorassociated antigen. [81] Mice with CT26 tumors were immunized with DCs co-transfected with GM-CSF mRNA and CT26 whole tumor mRNA; the cytotoxic activity of immunized mice was significantly higher than that of the control group. [64] Mu et al reported that among 19 patients with androgen-resistant prostate cancer that were treated with total tumor-derived mRNA loaded DC vaccines, 8 patients progressed, 11 patients were considered to have stable disease, and 13 patients showed a decrease in serum prostate-specific antigen levels.…”
Section: Dcs Pulsed/enveloped With Whole Tumor Rnamentioning
confidence: 96%
“…[ 80 ] This strategy was applied to acute myeloid leukemia; it resulted in the induction of leukemia‐specific cytotoxic T lymphocytes and the identification of B1‐1 peptide as a novel immunogenic tumor‐associated antigen. [ 81 ] Mice with CT26 tumors were immunized with DCs co‐transfected with GM‐CSF mRNA and CT26 whole tumor mRNA; the cytotoxic activity of immunized mice was significantly higher than that of the control group. [ 64 ] Mu et al.…”
Section: Cancer Vaccines Loaded With Part Of Whole Tumor Antigensmentioning
confidence: 99%
“…Polymeric NPs are nanosized particles composed of polymeric materials . The PNPs have numerous benefits over conventional antimicrobial agents, including enhanced drug stability, bioavailability, solubility, and sustained release. , They have also been extensively investigated for their anti-biofilm and antibacterial activity . Polymeric NPs can be prepared using several techniques such as solvent evaporation, emulsion, and nanoprecipitation.…”
Section: Nanotechnological Approaches For Biofilm Controlmentioning
confidence: 99%
“…In particular, stimuli-responsive polymeric nanovaccines have become a trend in immunotherapeutic applications due to their excellent targeting capabilities and safety, providing satisfactory biosafety and desirable therapeutic effectiveness. 40 This review aims to present the latest development of stimuli-responsive polymeric nanovaccines used in immunotherapy (Scheme 1). Based on recent research, these polymeric nanovaccines are described and categorized into categories, with a specific emphasis on the distinctive material properties and underlying mechanism toward immunotherapy, including polymeric nanovaccine systems that respond to pH, temperature, redox, photothermal, and ultrasound (Table 1).…”
Section: Introductionmentioning
confidence: 99%